Synthesis, characterization, purity verification, antiplasmodial activity and toxicity against Artemia salina Leach of salicylhydrazones and p-tosylhydrazones from S-(+)-carvone and arylketones - Atchade, Bardieu; KPOVIESSI DOSSOU, SIKA SALOME; Gbaguidi, A. Fernand; GLINMA, BIENVENU; Ahoussi, Léon A.; GBENOU, Joachim; Accrombessi, Georges C.; Frederick, Raphaël; Poupaert, Jacques H. (My University, 2015)
Hydazones are molecules that inhibit the development of several microbes and parasites. They are known for their pharmacological activities: antimicrobial, antiviral, antitumor, antimalarial, Anticonvulsant. In this research, we synthesized with good yields(57-91%), substituted hydazones of 4'-methylacetophenone, 2-acetonaphthone, 7methoxy-1-tetralone andS (+)-carvone that formed two series: the series of salicylhydrazones(1a- 4a) and the series of p-tosylhydrazones of (1b-4b). Then we checked purity of molecules by elemental and HPLC analysis. Spectrometric analyzes methods such as HRMS, 1HNMR and 13C were used to confirm their structures. Their antiparasitic properties were evaluated on Plasmodium falciparum and the toxicity against Artemia salina Leach. Molecules of salicylhydrazones series presented moderate activity with good selectivity (7≤ SI ≤ 14). All compounds were found non-toxic to the larvae except 1a, 3b and 4b. In view of the observed activities and those already known, hydrazones could be a promising approach to the treatment of malaria.
Keywords: Synthesis; hydrazones; aryl ketone; purity; antiplasmodial activity; selectivity